2020
DOI: 10.1111/myc.13102
|View full text |Cite
|
Sign up to set email alerts
|

Adult tinea capitis in China: A retrospective analysis from 2000 to 2019

Abstract: Summary Background Tinea capitis (TC) is an infection of the scalp hair due to dermatophytes. Most commonly seen in prepubescent children, but data of adults tinea capitis (ATC) in China mainland are limited. Objectives We aimed to evaluate epidemiological, clinical and mycological characteristics of ATC in China from 2000 to 2019. Methods We retrospectively analysed all ATC reported cases in China mainland, confirmed by mycological examination, by searching PubMed, Wanfang, Weipu and CNKI database. Results In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
46
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 18 publications
4
46
2
2
Order By: Relevance
“…The annual incidence of adult TC also varies among countries, and the incidence may be the highest in Taiwan in accordance with our understanding. Liang et al collected 269 cases in 20 years (13.5 cases per year), 29 Park et al 3 collected 82 adult cases during an 18‐year period (4.5 cases per year) and Diop et al 2 collected 121 in 6 years (20.2 cases per year), while we collected 104 adult TC in merely 4.5 years (23.1 cases per year). One possible explanation is that adult TC has been underestimated in other countries.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The annual incidence of adult TC also varies among countries, and the incidence may be the highest in Taiwan in accordance with our understanding. Liang et al collected 269 cases in 20 years (13.5 cases per year), 29 Park et al 3 collected 82 adult cases during an 18‐year period (4.5 cases per year) and Diop et al 2 collected 121 in 6 years (20.2 cases per year), while we collected 104 adult TC in merely 4.5 years (23.1 cases per year). One possible explanation is that adult TC has been underestimated in other countries.…”
Section: Discussionmentioning
confidence: 73%
“…The pathogen prevalence of adult TC depends on the regional‐specific epidemiology in different geographic areas. For example, Diop et al 2 revealed that the predominant pathogens in adult TC were anthropophilic T. soudanense (65.0%) and anthropophilic M. audouinii (21.0%) in Senegal, while M. canis , T. violaceum and T. rubrum were the main pathogens of TC in China, South Korea and Taiwan 3,16,29 . T. soudanense and M. audouinii have been reported infrequently in Asia because these pathogens are not endemic, but they have been reported to cause TC in South and West Asian countries such as Pakistan, Nepal and Kuwait 18,30,31 …”
Section: Discussionmentioning
confidence: 99%
“…The distribution of pathogens varies geographically worldwide 14 . Liu et al 15 results showed that M .…”
Section: Discussionmentioning
confidence: 99%
“…In mainland China, adults took up 6.0–13.6% of the tinea capitis population in the 1980s–1990s [ 12 ]. This number remained to be 9.0% in the 21th century [ 13 ]. In contrast, up to 63% of tinea capitis patients were reported to be adults in a single centre of Taiwan, China [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…These indicate that adult tinea capitis is becoming less uncommon in some regions, especially in postmenstrual elder women, due to their reduced secretion of fungistatic sebum after menopause. In adult patients, the female-to-male ratio was reported to be 2.2–5.4:1 [ 4 – 6 , 11 , 13 , 15 ] and 26.7–93.5% of the female adults were postmenopausal [ 10 , 11 ]. Apart from severe immunosuppressive diseases such as HIV infection and post-transplantation, systemic chronic disease including HCV infection (34.4%) and diabetes mellitus (22.4%) has been reported to associate with tinea capitis [ 6 ].…”
Section: Discussionmentioning
confidence: 99%